2001
DOI: 10.1021/ci0100503
|View full text |Cite
|
Sign up to set email alerts
|

QSPR Correlation of the Melting Point for Pyridinium Bromides, Potential Ionic Liquids

Abstract: In an attempt to develop predictive tools for the determination of new ionic liquid solvents, QSPR models for the melting points of 126 structurally diverse pyridinium bromides in the temperature range 30-200 degrees C were developed with the CODESSA program. Six- and two-descriptor equations with squared correlation coefficients (R(2)) of 0.788 and 0.713, respectively, are reported for the melting temperatures. The models illustrate the importance of information content indices, total entropy, and the average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(163 citation statements)
references
References 27 publications
5
156
0
2
Order By: Relevance
“…Equations 1 and 2 are also similar to melting-point QSARs derived for other ionic liquids in that they involve hydrogen-bond descriptors and NRI. 9,17 Ten excellent, single-descriptor QSPRs were derived for the densities of the bromide salts and are displayed in Table 5. Most descriptors include either various measures of hydrogen-bonding capability or have to do with the partial atomic charge distribution and are interpreted as characterizing the interactions between ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equations 1 and 2 are also similar to melting-point QSARs derived for other ionic liquids in that they involve hydrogen-bond descriptors and NRI. 9,17 Ten excellent, single-descriptor QSPRs were derived for the densities of the bromide salts and are displayed in Table 5. Most descriptors include either various measures of hydrogen-bonding capability or have to do with the partial atomic charge distribution and are interpreted as characterizing the interactions between ions.…”
Section: Resultsmentioning
confidence: 99%
“…19 The resulting melting-point QSPRs have r 2 values ranging from 0.690-0.788, except for the QSPR derived for a subset of 18 substituted imidazolium bromides, which has an r 2 value of 0.943. 9,17 Liquid-density QSPRs have been previously derived for alkanes in two studies. 20,21 In the first study, structural descriptors computed from molecular graphs were used to derive physical properties, including liquid density, for 134 alkanes.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the individual points are taken into consideration, some very interesting results emerge. For instance, it can be noticed that methanol (45) and methylamine (77), ethanol (46) and ethylamine (78), and 1-propanol (47) and 1-propylamine (79) lay very close to each other, especially in the plot of trial III. This should mean that, in the representational space, an alkanol is much more similar to a primary amine with the same number of carbon atoms than to the corresponding superior homologous one.…”
Section: Resultsmentioning
confidence: 92%
“…CODESSA PRO has been successfully applied to a large variety of problems. 22,23,[44][45][46] In recent years, various approaches have been taken into consideration to realize the function g by more complex machine-learning models such as the neural networks. 24,41,47 NNs, in fact, are powerful data modeling tools able to approximate nonlinear relationships among chemical structural parameters and physical-chemical properties.…”
Section: Prediction Of the Solvation Free Energymentioning
confidence: 99%
“…Two separate studies were reported for pyridinium, [22] and benzylimidazolium bromides. [23] Melting point data were withdrawn from the Beilstein database and ranged from 30 to 370 ºC.…”
Section: Reports On Modelling Melting Point For Ionic Liquidsmentioning
confidence: 99%